2020
DOI: 10.1021/acs.orglett.0c03151
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Addition/Cyclization of (2-Hydroxyaryl)boronic Acids with Alkynylphosphonates: Access to Phosphacoumarins

Abstract: A facile palladium-catalyzed addition/cyclization of (2-hydroxyaryl)­boronic acids with alkynylphosphonates has been developed, providing an effective strategy to construct a series of valuable phosphacoumarins. This methodology features excellent regioselectivity and broad substrate tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…This experiment demonstrated that water and PhB­(OH) 2 are the sources of the proton . Based on the control experiment and previous literature, a plausible catalytic cycle for this new transformation is proposed in Scheme . ,, We speculate that the reaction is initiated by the formation of Pd­(II) complex ( I ) with 1,3-dicarbonyl alkyne in the presence of potassium acetate. Subsequently, the Pd­(II) complex undergoes trans-metalation of the boronic acid to afford the complex II by the loss of acetoxy boric acid, which was confirmed by mass spectral analysis.…”
mentioning
confidence: 77%
“…This experiment demonstrated that water and PhB­(OH) 2 are the sources of the proton . Based on the control experiment and previous literature, a plausible catalytic cycle for this new transformation is proposed in Scheme . ,, We speculate that the reaction is initiated by the formation of Pd­(II) complex ( I ) with 1,3-dicarbonyl alkyne in the presence of potassium acetate. Subsequently, the Pd­(II) complex undergoes trans-metalation of the boronic acid to afford the complex II by the loss of acetoxy boric acid, which was confirmed by mass spectral analysis.…”
mentioning
confidence: 77%
“…24 However, to the best of my knowledge, there are few reports regarding the electrochemical cyclic enol phosphonate synthesis. 16 In continuation of our project on sustainable electrochemical functionalization of unsaturated C−C bonds, 25 herein, we report an unprecedented electrochemical tandem selenation or halogenation cyclization (Scheme 1c). 26 Notable features of our method include (1) unprecedented electrochemical cyclic enol phosphonate construction, (2) the absence of any transition metal catalyst and chemical oxidants, (3) valuable and tunable selenoether or halogen-functionalized cyclic enol phosphonates, which allow further diversification, 27 (4) broad substrate scope and compatibility with complex natural products and bioactive molecules, and (5) detailed mechanistic insights.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 Phosphacoumarin 13 was generated via palladium-catalyzed addition and cyclization of 2-hydroxyphenylboronic acid with alkynylphosphinate 4a (Scheme 6f). 14 In summary, we developed an exceptionally mild, efficient, and metal-free three-component coupling reaction involving arynes, phosphites, and alkynes to afford aryl(alkynyl)phosphinates. The reaction proceeded smoothly with both aryl and aliphatic group-substituted acetylenes.…”
mentioning
confidence: 99%
“…Additionally, β-ketophosphonate-substituted phosphinate 12 was synthesized via palladium-catalyzed hydration of 4a (Scheme e) . Phosphacoumarin 13 was generated via palladium-catalyzed addition and cyclization of 2-hydroxyphenylboronic acid with alkynylphosphinate 4a (Scheme f) …”
mentioning
confidence: 99%